Developmental basis of phenotypic integration in two Lake Malawi cichlids. Issue 1 (December 2016) - Le Pabic, Pierre; Cooper, W.; Schilling, Thomas
Abstract Background Cichlid fishes from the Rift Lakes of East Africa have undergone the most spectacular adaptive radiations in vertebrate history. Eco-morphological adaptations in lakes Victoria, Malawi and Tanganyika have resulted in a vast array of skull shapes and sizes, yet primary axes of morphological variation are conserved in all three radiations, prominently including the size of the preorbital region of the skull. This conserved pattern suggests that development may constrain the trajectories of cichlid head morphological evolution. Results Here, we (1) present a comparative analysis of adult head morphology in two sand-dweller cichlids from Lake Malawi with preorbital size differences representative of the main axis of variation among the three lakes and (2) analyze the ontogeny of shape and size differences by focusing on known developmental modules throughout the head. We find that (1) developmental differences between the two species correlate with known developmental modules; (2) differences in embryonic cartilage development result in phenotypically integrated changes among all bones derived from a single cartilage, while differences in dermal bone development tend to influence isolated regions within a bone; and lastly (3) species-specific morphologies appear in the embryo as subtle differences, which become progressively amplified throughout ontogeny. We propose that this amplification takes place at skeletal growth zones, the locations and shapes of which are patterned during embryogenesis. Conclusions This study is the most anatomically comprehensive analysis of the developmental differences underlying cichlid skull evolution in the Rift Lakes of East Africa. The scale of our analysis reveals previously unnoticed correlations between developmental modules and patterns of phenotypic integration. We propose that the primary axes of morphological variation among East African cichlid adaptive radiations are constrained by the hierarchical modularity of the teleost head skeleton.